Pengaruh Evaluasi Kurikulum Terhadap Peningkatan Kualitas Pembelajaran Di SMKN 12 Malang - Nurul Qomariyah; Zahrotul Mufarihah; Aditya Putra Ayuni (Indonesian Journal of Islamic Educational Management, 2025)
Curriculum evaluation is a systematic process aimed at assessing the effectiveness of the curriculum in achieving educational objectives while providing a basis for improving the quality of learning. This study aims to analyze the influence of curriculum evaluation on improving the quality of learning in educational institutions. The research method used is descriptive qualitative and literature study. The results show that curriculum evaluation at SMKN 12 Malang plays an important role in measuring the achievement of learning objectives, providing constructive feedback for teachers and students, ensuring the validity and reliability of the learning process, and serving as a basis for curriculum innovation and development. In addition, the implemented curriculum evaluation also strengthens real-life skills-based learning and increases the accountability of educational institutions to stakeholders. In conclusion, the implementation of systematic and continuous curriculum evaluation contributes significantly to increasing the effectiveness, relevance, and quality of learning in an era of dynamic educational change